Analysis of Financial Performance Before and After Going Public (Case Study of Companies Listed in 2020 on the Indonesian Stock Exchange) - Siregar, Ahlan Jefri; Pasaribu, Dompak; Sembiring, Yosephine N.; Simanjuntak, Arthur (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to test and analyze the company's financial performance in terms of liquidity, activity, profitability and solvency aspects before and after going public and being listed on the IDX. A population of 51 companies listed on the IDX in 2020, a total of 22 companies were used as samples in this study. The sampling technique used is the purposive sampling method. The data used in this research was obtained from visits to www.idx.co.id and the company's main website. The collected data was then run using the SPSS version 26 program. The research found that the current ratio and net profit margin, two measures of a company's financial health, changed significantly between the pre-IPO and post-IPO periods. Financial metrics such as total asset turnover and debt-to-equity ratio did not change between the pre- and post-IPO periods for the company.